Fiscal Decentralization, Government Behavior, and Environmental Pollution: Evidence From China - Cai, Hongying; Tong, Zefeng; Xu, Shulin; Chen, Shuoqi; Zhu, Peng; Liu, Wenjie (Frontiers in Environmental Science, 2022)
Environmental protection is a basic public service that the government must guarantee and is closely related to public health. An important driver of environmental pollution in China is the local government’s pursuit of a rapid economic development while ignoring environmental protection under the Chinese-style fiscal decentralization system. On the basis of the principal–agent theory between the central and local governments, this study analyzes the environmental deterioration caused by the distortion of local government behavior under fiscal decentralization. In addition, using China’s prefecture-level city data from 2014 to 2018, this study empirically estimates the impact of fiscal decentralization on environmental pollution. SO2 emissions and PM2.5 concentrations are used to measure the degree of environmental pollution. Results show that Chinese-style fiscal decentralization exacerbates environmental pollution and that the impact of fiscal decentralization on environmental pollution differs in regions with varying levels of economic development and cultural penetration. Moreover, fiscal decentralization does not significantly impact environmental pollution in eastern China and in those areas influenced by Confucian culture yet aggravates the environmental pollution in central and western China and in those areas that are not affected by Confucian culture. These results offer important policy implications. Clearly dividing the power and financial power between the central and local governments, establishing an environmental governance system compatible with economic incentives, and establishing an environmental public finance system can alleviate the impact of Chinese-style fiscal decentralization on environmental pollution.